Re-evaluation of the Mesozoic–Cenozoic biostratigraphy of the Laurentian Subbasin of the Scotian Basin, offshore eastern Canada - Weston, Janice F.; MacRae, R. Andrew; Ascoli, Piero; Cooper, M. Kevin E.; Fensome, Robert A.; Shaw, David; Williams, Graham L. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2023)
We use new and existing nannofossil, palynological, and microfossil biostratigraphic data in conjunction with lithologic and geophysical logs from four wells to establish a series of sequence-stratigraphic events in the Mesozoic–Cenozoic of the Laurentian Subbasin of offshore Newfoundland, eastern Canada. Well biostratigraphic events are integrated with reflection seismic in the area to correlate regional seismic stratigraphic surfaces. The four wells are: Bandol-1, Emerillon C-56, East Wolverine G-37, and Heron H-73. We extend the event stratigraphic scheme previously developed for the Scotian Margin, offshore Nova Scotia, into new areas to the east along the southern Grand Banks, where we recognize four new well-log sequence stratigraphic events, and we modify the definition of a previously recognized regional surface. The new and modified regional surfaces are the Early Albian Unconformity, the Late Bathonian Maximum Flooding Surface (MFS), the Late Bajocian MFS (renamed from Bathonian/Bajocian MFS), the ?Bajocian/Toarcian Unconformity, and the Late Pliensbachian MFS. We recognize the "Avalon Unconformity" and "Base-Tertiary Unconformity" of previous studies as amalgamations of multiple smaller-scale unconformities and refine their age in the studied wells. A major improvement over our earlier Scotian Margin event schemes is the extension of the event stratigraphy into the Early Jurassic using a suite of marine biostratigraphic markers. We compare the Early Jurassic event scheme to Deep Sea Drilling Project Site 547B on the conjugate Moroccan Margin to better constrain potential source rock intervals and the early history of the central Atlantic Ocean.